Food and feeding habits of the mahseer, Tor putitora (Hamilton - Gupta, M Das (Indian Journal of Fisheries, 2011)
Though some work on the food and feedinghabits of Tor putitora has been done elsewhere(Sehgal et al. 1971, Das and Pathani1978 and Nautiyal and Lai 1984) but so farthere is no report on this aspect from theNorth-Eastern India. The present study was,therefore, undertaken.